Physical activities for moral forming football athletes - Ahmad Atiq; Wiwik Yunitaningrum (H.S. Skovoroda Kharkiv National Pedagogical University, 2020)
Aim: to determine the level of implementation of physical activity in the formation of moral football athletes. Material and methods. The method used in this research is descriptive research, with a quantitative approach. The research instrument used interviews, observation and observation sheets, as well as documentation. The method used in this study is a descriptive method with survey research forms. The population in this study amounted to 16 athletes. This research uses a Likert scale. Results. Based on the results of research and discussion of physical activities for moral forming football athletes, it can be concluded that: (1) Moral Knowing, it can be concluded into 4 categories, namely very good at 3.2%, good at 53.2%, enough for 39.2%, and less at 4.3%. The category difference between very good and good is 50%. Meanwhile, the moderate and insufficient categories had a difference of 34.9%. There is absolutely no or 0% lack for the category. (2) Moral Action can be concluded into 3 categories, namely very good at 26.9%, both 53.2% and 19.9% ​​sufficient. Meanwhile, for the less and less category, it was 0%. (3) Moral Feeling can be concluded into 3 categories, namely very good at 41.4%, good at 48.4% and quite 10.2%. Meanwhile, for the category of less and less at 0%. So the results of this study can be concluded that to form a person's character through sports, one of which is through football. Then it can be seen in the results of the study that physical activity to shape the character of soccer athletes in Pontianak is in the good category. If athletes want to develop into professional athletes, they must be able to form good personal character. Conclusions. Athletes must have morals that are formed when doing physical activities such as branching sports that is having knowledge about morals, having feelings about morals and having good moral habits. This can be demonstrated by carrying out physical activities according to the trainer's direction, having a special schedule to carry out physical activity, teamwork, self-knowledge, the spirit of fairplay competence, decision making, and an attitude of empathy